Role of Female Community Health Volunteers for Prevention and Control of COVID-19 in Nepal - Parajuli, Surya B.; Shrestha, Sabin; Sah, Anisha; KC, Heera; Amgain, Kapil; Pyakurel, Prajjwal (Journal of Karnali Academy of Health Sciences, 2020)
Female Community Health Volunteers (FCHVs) are the pillars of community health programs in Nepal who play a pivotal role in implementing various community based preventive, promotive, and curative health programs. In the context of COVID 19 pandemic and possible outbreak in Nepal, the only way by which it can be stopped at the moment is by prevention. This paper presents the role of FCHVs for the prevention and control of COVID 19 in Nepal.